Aplikasi Lean Manufakturing dan Junbiki System Sebagai Upaya Perbaikan Berkelanjutan on Time Delivery di Perusahaan Manufakturing Otomotif - Esthadi Wahyu Septony; Putu Dana Karningsih (LPPM Institut Pendidikan Nusantara Global, 2026)
In the automotive manufacturing industry, on-time delivery (OTD) is a key sign of how reliable operations are. Not only do activities on the assembly line affect OTD performance, but so do the effectiveness of internal logistics in making sure that material flow meets production needs. This study examines the implementation of Lean Manufacturing through the integration of Value Stream Mapping (VSM) and the Junbiki system as a pull-by-sequence approach to enhance internal logistics performance and stabilize on-time delivery (OTD). A case study methodology is employed, concentrating on the internal logistics process for large-part distribution within an automotive manufacturing firm. The research commences with Current Value Stream Mapping (CVSM) to pinpoint waste, subsequently leading to the creation of Future Value Stream Mapping (FVSM) and the execution of the Junbiki system. To see if performance has improved, we look at the logistics lead time and material flow conditions before and after implementation. The Junbiki system cut the total logistics lead time by 60.5%, from 315.2 minutes to 124.4 minutes. This improvement was made by getting rid of delays in getting information, cutting down on double handling, making transportation routes easier, and cutting down on wait times caused by too much inventory. As a result, the flow of materials became more in sync with assembly operations, which made OTD performance more consistent. This study emphasizes the significance of sequence-based material flow control via the Junbiki system in enhancing production reliability. However, as a singular case study, the results are particular to the observed context and must be utilized with regard to varying logistics and production circumstances.